2014
DOI: 10.1186/s13023-014-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of primary adrenal insufficiency in Zellweger spectrum disorders

Abstract: Zellweger spectrum disorders are a group of autosomal recessive disorders characterized by impaired peroxisome functions. The clinical spectrum is broad, ranging from the classical most severe Zellweger syndrome to patients with a relatively mild phenotype. Treatment options are limited to symptomatic and supportive therapy. During routine follow-up we discovered patients with asymptomatic primary adrenal insufficiency. It is important to detect impaired adrenal function because it has treatment implications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…A recent study reported a high prevalence of primary adrenal insufficiency in a population of 29 PBD-ZSD patients [76]. It is recommended that after one year of age, yearly (or more frequent) adrenal monitoring with adrenocorticotropic hormone (ACTH) and morning cortisol be performed.…”
Section: Management and Treatment Guidelinesmentioning
confidence: 99%
“…A recent study reported a high prevalence of primary adrenal insufficiency in a population of 29 PBD-ZSD patients [76]. It is recommended that after one year of age, yearly (or more frequent) adrenal monitoring with adrenocorticotropic hormone (ACTH) and morning cortisol be performed.…”
Section: Management and Treatment Guidelinesmentioning
confidence: 99%
“…This chronic accumulation of cholesterol with saturated VLCFA is believed to result in apoptosis and ultimately atrophy of the adrenal cortex, with loss of cortisol production 41 . Notably, adrenal insufficiency has also been reported in patients with a Zellweger spectrum disorder 42,43 , who also accumulate VLCFA in their adrenal glands. This observation, therefore, lends further support to the notion that VLCFA accumulation is important in the pathophysiology of adrenal insufficiency.…”
mentioning
confidence: 93%
“…We follow a phenotypically and genetically heterogeneous cohort of ZSD patients at the Academic Medical Centre in Amsterdam . All patients are regularly examined including physical exams and laboratory check‐ups.…”
Section: Methodsmentioning
confidence: 99%
“…We follow a phenotypically and genetically heterogeneous cohort of ZSD patients at the Academic Medical Centre in Amsterdam. [6][7][8] All patients are regularly examined including physical exams and laboratory check-ups. Typically, examinations also include abdominal ultrasounds and for almost all patients results of a magnetic resonance imaging (MRI) of the brain is available.…”
Section: Patientsmentioning
confidence: 99%